Moderating Effect of Good Governance on Determinants of the Quality Region Government Financial Reports - Pattiasina, Victor; Noch, Muhamad Yamin; Rumasukun, Muhammad Ridwan; Seralurin, Yohanes Cores; Tamaela, Eduard Yohannis (E-Jurnal Akuntansi; Vol 32 No 10 (2022), 2022)
The purpose of this study was to analyze the effect of Accrual-Based Government Accounting Standards (GAS) implementation, apparatus competence and the role of internal audit on the quality of local government financial statements with good governance as a moderating variable. This type of research is ekspanatory research. The population in this study were auditors who worked at the Financial and Development Supervisory Agency (BPKP) Representative of Papua Province, totalling 91 auditors. The technique for determining the sample was by using purposive sampling with the final sample was 74 respondents. Hypothesis testing uses multiple regression analysis and residual test for moderating variables with the help of the SPSS program. The results of this study prove that the implementation of accrual-based GAS has an positive dan significant effect on the quality of local government financial reports, apparatus competence has no effect on the quality of local government financial reports, the role of internal audit does not affect the quality of local government financial reports, good governance as a moderating variable can moderate the relationship between accrual-based GAS implementation. Keyword: Accrual-Based GAS Application; Apparatus Competence; Internal Audit Role; Good Governance; Financial Report Quality